PELAYANAN WAITER SADAA RESTO LABERSA HOTEL & COVENTION CENTRE TOBA DI BALIGE - Hutabalian, Jones Kevin Melkianus; ', Etika (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to determine how the waiter service is at SadaaResto, Labersa Hotel & Convention Center Toba, Balige, North Sumatra. Excellent service is the main key in creating customer satisfaction, especially in the hotel industry. This study uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. Informants consist of hotel management, waiters, and consumers who have used Sadaa Resto services. The results of the study indicate that the waiter service at Sadaa Resto has reflected several dimensions of service quality such as physical evidence (tangible), empathy, responsiveness, reliability, and assurance. Waiters at Sadaa Resto show a friendly, professional, and responsive attitude to customer complaints. However, several obstacles such as late serving and supporting facilities that still need to be improved were also found. This study emphasizes the importance of the role of waiters in forming a positive dining experience and contributing to customer loyalty and the overall image of the hotel. Keywords: Waiter Service, Service Quality, Sadaa Resto,